2008
DOI: 10.1016/j.jaut.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Cell damage and autoimmunity: A critical appraisal

Abstract: In April 2007, an international Colloquium bridging scientific and clinical disciplines was held to discuss the role of cellular and tissue damage in the initiation, development and persistence of autoimmune disease. Five potential etiologic and pathophysiologic processes fundamental to autoimmune disease (i.e. inflammation, infection, apoptosis, environmental exposure and genetics) were the focus of the presentations and integrative discussions at the Colloquium. The information presented on these topics is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 87 publications
1
100
0
8
Order By: Relevance
“…It has been suggested that the principal event leading to inflammatory diseases is cell damage as a result of apoptosis or necrosis (36,52,56). Increased permeability of the epithelial barrier and increased apoptotic rates of epithelial cells have been implicated to be major factors in the pathogenesis of intestinal inflammation (25,64).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the principal event leading to inflammatory diseases is cell damage as a result of apoptosis or necrosis (36,52,56). Increased permeability of the epithelial barrier and increased apoptotic rates of epithelial cells have been implicated to be major factors in the pathogenesis of intestinal inflammation (25,64).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been implicated in the pathogenesis of autoimmune disorders, including altered apoptosis [245]. Although autoimmunity may not follow impaired clearance of apoptosing cells [70,246,247], many studies show that such an impairment may result in immunogenicity and autoimmune disorders.…”
Section: Secondary Necrosis In Autoimmune Diseasesmentioning
confidence: 99%
“…The direct causes of autoimmune diseases remain unclear, but it is known that in addition to genetic factors, environmental triggers such as viruses, bacteria and other pathogens can participate in the development of autoimmune diseases [57]. Autoimmunity is also closely associated with inflammation, although the role of inflammation in the development of autoimmunity is still a subject of investigation [59]. In many autoimmune and infectious diseases (rheumatoid arthritis (RA), active Crohn's disease, tuberculosis, Lyme disease, sarcoidosis, etc.…”
Section: Sialylation α-13-galactosylation and Microorganismsmentioning
confidence: 99%